2016
DOI: 10.18632/oncotarget.12138
|View full text |Cite
|
Sign up to set email alerts
|

miR-135b expression downregulates Ppm1e to activate AMPK signaling and protect osteoblastic cells from dexamethasone

Abstract: Activation of AMP-activated protein kinase (AMPK) could potently protect osteoblasts/osteoblastic cells from dexamethasone (Dex). We aim to induce AMPK activation via microRNA (“miRNA”) downregulation of its phosphatase Ppm1e. We discovered that microRNA-135b (“miR-135b”) targets the 3' untranslated regions (UTRs) of Ppm1e. In human osteoblasticOB-6 cells and hFOB1.19 cells, forced-expression of miR-135b downregulated Ppm1e and activated AMPK signaling. miR-135b also protected osteoblastic cells from Dex. shRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 39 publications
2
87
0
Order By: Relevance
“…It belongs to the Ppm family [34,35]. Our previous study demonstrated that microRNA-135b downregulated Ppm1e expression to activate AMPK signaling, which in turn protected osteoblastic cells from Dex-induced injuries [4]. In the present study, our results suggest that Lnc-MALAT1 protects human osteoblasts from Dex-induced injury via activation of Ppm1e-AMPK signaling.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…It belongs to the Ppm family [34,35]. Our previous study demonstrated that microRNA-135b downregulated Ppm1e expression to activate AMPK signaling, which in turn protected osteoblastic cells from Dex-induced injuries [4]. In the present study, our results suggest that Lnc-MALAT1 protects human osteoblasts from Dex-induced injury via activation of Ppm1e-AMPK signaling.…”
Section: Introductionsupporting
confidence: 68%
“…Quantitative real-time polymerase chain reaction assay As described previously [4,38], TRIzol reagent was used to extract total cellular RNA, which was then reverse-transcribed. cDNA was then amplified by quantitative real-time polymerase chain reaction (qPCR).…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations